Malabār Kalāpaṃ, 1921 : smaraṇakaḷuṃ paṭhanaṅṅaḷuṃ (Malabār Kalāpaṃ 1921 60-āṃ Vārṣikāghōṣa Kammaṯṯi, 1981)
60th year commemoration volume of the 1921 Malabar Rebellion against British rule; comprises contributed articles.